2009
DOI: 10.1021/ja905637y
|View full text |Cite
|
Sign up to set email alerts
|

Widening the View on Dispersant−Pigment Interactions in Colloidal Dispersions with Saturation Transfer Difference NMR Spectroscopy

Abstract: The application of Saturation Transfer Difference (STD) NMR spectroscopy for the characterization of dispersant particle interactions is introduced. STD NMR has hitherto been applied, with great success, to the characterization of ligand-protein interactions and is currently a standard tool in biomolecular NMR spectroscopy. Nevertheless, the STD NMR technique has so far not yet crossed the boundaries of the biomolecular field. Here, we demonstrate that in spite of clear differences between a protein binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…used saturation‐transfer difference (STD) NMR to investigate the association between amino acids and the polystyrene surface . STD NMR is similar to DEST in that off‐resonance saturation is used to monitor the strength of binding in an invisible, NP‐bound state. Aromatic amino acids exhibited the strongest STD effect, suggesting that significant π‐π interactions can occur between amino acid side chains and the NP surface.…”
Section: Results From Different Nanoparticle Systemsmentioning
confidence: 99%
“…used saturation‐transfer difference (STD) NMR to investigate the association between amino acids and the polystyrene surface . STD NMR is similar to DEST in that off‐resonance saturation is used to monitor the strength of binding in an invisible, NP‐bound state. Aromatic amino acids exhibited the strongest STD effect, suggesting that significant π‐π interactions can occur between amino acid side chains and the NP surface.…”
Section: Results From Different Nanoparticle Systemsmentioning
confidence: 99%
“…Furthermore, as ligand protons in close contact with the protein receive more saturation than more distant ones, the relative intensity of the ligand resonances can be interpreted in terms of a binding epitope. Despite the broad information that this technique could provide in supramolecular systems, it has been almost exclusively utilized in protein–ligand studies and only a few studies have been performed on synthetic hosts 46 47 . Here we demonstrate the potential of STD NMR for the investigation of interactions between hybrid metal-organic Al-ITQ-HB and several substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have used Saturation‐Transfer Difference (STD) NMR to examine the binding between small molecules and the surface of polystyrene (PS) nanoparticles. STD‐NMR is a ligand‐detected technique that has been widely used to detect small molecule ligands binding to protein receptors; in our recent study, we showed that this technique can be extended to consider PS nanoparticles as the “receptor.” An advantage of the STD‐NMR technique is that by comparing the relative STD effect for nuclei in the ligand, structural information regarding the binding epitopes of that ligand can be determined as well …”
Section: Introductionmentioning
confidence: 99%